2003
DOI: 10.1007/s00216-003-1811-7
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy for detection of the different Si–O bonding states of silicon

Abstract: X-ray photoelectron spectroscopy (XPS) was used to detect the bonding between a silica particle surface and attached silanes. In addition to the commonly recorded Si 2p spectrum, the Si 1 s level is also accessible when monochromatic Ag Lalpha X-rays are applied. Furthermore, the spectrum of the Si 1 s level shows a fine structure. After spectrum deconvolution, we assigned the fitted spectral peaks to Si-C bonds of the silanes and to the Si-O bonds of the silica network. The recorded Si 1 s spectra were deconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…8). Such a peak appearance can be attributed to the adsorption of organosi- [17]. The presence of Me-OSi-R structures in the polymer-grafted surfaces (Al-A PMVK and Al-V PMVK) strongly indicates that the siloxane layer is preserved during polymer grafting.…”
Section: Chemical Characterization Of Modified Aluminum Surfacesmentioning
confidence: 90%
“…8). Such a peak appearance can be attributed to the adsorption of organosi- [17]. The presence of Me-OSi-R structures in the polymer-grafted surfaces (Al-A PMVK and Al-V PMVK) strongly indicates that the siloxane layer is preserved during polymer grafting.…”
Section: Chemical Characterization Of Modified Aluminum Surfacesmentioning
confidence: 90%
“…The energy difference between the Si 2p 3/2 and Si 2p 1/2 levels is *0.5 eV, causing the two peaks to overlap [19]. Fig.…”
Section: Si 2p Binding Energiesmentioning
confidence: 97%
“…Fig. 4 FT-IR spectra of the inorganic polymer recorded after 3 weeks compared to a spectra recorded after 1 year peak intensities has been determined experimentally to 0.52 in a high-resolution XPS investigation of the metallic component of a clean silicon wafer compared to a theoretical ratio of 0.5 [19]. Comparison of the metallic and oxidized silicon species has shown that the Si-O-Si composite peak is broadened and does not show a resolved structure.…”
Section: Si 2p Binding Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy difference between the Si 2p 3/2 and Si 2p 1/2 levels is ³0.5 eV causing the two peaks to overlap. 40) The Si 2p spectra of pyrite samples are illustrated in Fig. 8.…”
Section: Effect Of Treatment Time Of Silicate Coating On Pyrite Oxidamentioning
confidence: 99%